GROWTH, YIELD AND QUALITY PERFORMANCE, NUTRITIONAL COMPOSITION AND THERAPEUTIC POTENTIAL OF CUCUMBER (CUCUMIS SATIVUS L.) OFF-SEASON PRODUCTION IN PLASTIC TUNNEL - Khalid Rahman; Muhammad Saleem Jilani; Jabbar Khan (Journal of Population Therapeutics and Clinical Pharmacology, 2024)
The study was aimed at enhancing yield and quality in terms of growth parameters using different doses of nitrogen supplementing nutritional composition and therapeutic potential of off-season cultivation of cucumber in plastic tunnels as a routine practice in certain areas of Pakistan. In this regard, study focused on improving the off-season production of  Monaliza cucumber in plastic tunnels in D.I.Khan division using different split doses of nitrogen (N2) with a constant amount of potassium (K) and phosphorus (P) with a purpose to enhance the cucumber yield and quality with the applications of various doses of nitrogen complementing nutritional and medicinal value by efficient management of N2 fertilizers. Cucumber seedlings were transferred to the plastic tunnel on the 6th day of their germination. A 150Kg/ha dose of N2 in the form of 2, 3, 4, and 5 equal split doses were applied along with a constant dose of 75 kg/ha of both P and K. The least days to flowering, fruit setting and fruit maturity were found with the application of four equal split doses of N2. Similarly, the maximum number of fruits per plant, maximum fruit length and fruit weight were obtained by using four  equal split doses of N2. Moreover the maximum yield was also obtained with application of four equal split doses of N2. The findings revealed that appropriate amount of N2 in four equal split doses in a combination of P and K had a significant effect on all the yield and quality parameters of Monaliza cucumber having nutritional and medicinal values